Optimal plant-wide control of the wet sulfuric acid process in an integrated gasification combined cycle power plant. (February 2019) - Husnil, Yuli Amalia; Andika, Riezqa; Lee, Moonyong
Highlights: Plant wide control of wet sulfuric acid (WSA) process in IGCC power plant was studied. A simple procedure to calculate minimum required hot air to combustor was utilized. Sensitivity analysis was implemented to find optimum set-points of major controlled variables of WSA process. Several controller schemes were proposed in achieving enhanced energy efficiency and operational stability. Abstract: This paper discusses plant-wide control system design of the wet sulfuric acid (WSA) process, which is part of an integrated gasification combined cycle power plant. The regulatory control structure, which ensures energy efficiency and operational stability, was designed by addressing the requirements and constraints of each key unit in the process. We used sensitivity analysis and simple stoichiometric calculation to obtain optimum set points for the controlled variables, which has a direct effect on the energy usage and production rate in the WSA process. In this work, we proposed several controller schemes that ensure efficiency and stability of the WSA process. The results of this work will contribute to improving the process efficiency, thereby facilitating energy efficient and stable operation of the WSA process.